The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1414-431x20155009
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant stress potentiates the preference for, and consumption of, ethanol induced by chronic pre-exposure to ethanol

Abstract: Ethanol abuse is linked to several acute and chronic injuries that can lead to health problems. Ethanol addiction is one of the most severe diseases linked to the abuse of this drug. Symptoms of ethanol addiction include compulsive substance intake and withdrawal syndrome. Stress exposure has an important role in addictive behavior for many drugs of abuse (including ethanol), but the consequences of stress and ethanol in the organism when these factors are concomitant results in a complex interaction. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Twenty-four hours after the last ethanol binge, basal anxiety in the light–dark apparatus was similar between ethanol-exposed and control mice. Others have reported withdrawal-induced anxiety in adolescent rats ( Pandey et al, 2015 ; Kyzar et al, 2016 ), although this is not consistently found ( Kiefer et al, 2003 ; Lee et al, 2016 ; Morais-Silva et al, 2016 ). Indeed, some have suggested that adolescent mice are resilient to early ethanol withdrawal ( Lee et al, 2016 ) and it is possible that binge ethanol in adolescence only produces lasting withdrawal-induced anxiety in rats and not mice.…”
Section: Discussionmentioning
confidence: 89%
“…Twenty-four hours after the last ethanol binge, basal anxiety in the light–dark apparatus was similar between ethanol-exposed and control mice. Others have reported withdrawal-induced anxiety in adolescent rats ( Pandey et al, 2015 ; Kyzar et al, 2016 ), although this is not consistently found ( Kiefer et al, 2003 ; Lee et al, 2016 ; Morais-Silva et al, 2016 ). Indeed, some have suggested that adolescent mice are resilient to early ethanol withdrawal ( Lee et al, 2016 ) and it is possible that binge ethanol in adolescence only produces lasting withdrawal-induced anxiety in rats and not mice.…”
Section: Discussionmentioning
confidence: 89%
“…Mice were individually placed in the middle of the arena and were allowed to explore freely the apparatus for 5 min. Analysis included measures of the distance travelled in central (central locomotion) and peripheral area (peripheral locomotion), as well as the total distance travelled (i.e., center + periphery) (total locomotion) [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ten min later, the object A’ was replaced by a rectangular object B, and the short-term memory was assessed. The long-term memory was evaluated 24 h later in the same apparatus by changing the object B by a new object, an orange sphere called object C. The same animals were evaluated for short- and long-term memory [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, behavioral crosssensitization is observed between stress and ethanol in both adolescent and adult rodents (for review, see Burke & Miczek, 2014). Stress exposure can raise ethanol intake and preference in both animals (Morais-Silva, Fernandes-Santos, Moreira-Silva, & Marin, 2016;Norman et al, 2015;Quadir et al, 2016) and humans (Sinha, 2001), although some studies have shown no impact of stress or a reduction in ethanol intake when rodents have access to alcohol during or immediately after stress (van Erp & Miczek, 2001;Marianno, Abrahao, & Camarini, 2017). Stress exposure also increases behavioral sensitivity to ethanol (Quadir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%